The Shaker Experience in America: A History of the United Society of Believers - Reid-Maroney, Nina (Labour / Le Travail, 1994)
The article reviews the book, "The Shaker Experience in America: A History of the United Society of Believers," by Stephen Stein.
Keywords: BOOKS -- Reviews; Nonfiction; SHAKER Experience in America: A History of the United Society of Believers, The (Book); SHAKERS; STEIN, Stephen